Multi-data source-based recycling value estimation of wasted domestic electrical storage water heater in China. (1st March 2022) - Wang, Fang; Liu, Qiming; Yu, Lean; Wang, Yanni
Highlights: A multi-data source-based hybrid methodology was developed. A novel seasonal grey model considering seasonal trend trait was proposed. The recycling value of wasted DESWH from 2012Q1 to 2038Q4 was analysed. Abstract: A domestic electrical storage water heater (i.e., DESWH) is one of the 14 products listed in China's Waste Electrical and Electronic Products Disposal Catalogue (Batch 2). Due to the lack of systematic quantitative analysis on the waste quantity and recovery value of a DESWH, a multi-data source-based hybrid methodology based on quarterly sales data, survey data and internet data is proposed. In the methodology, the seasonal Mann-Kendall trend test is used to identify the seasonal trait of the quarterly sales data for DESWHs, and an accurate prediction of the sales volume of DESWHs is obtained via a generalised seasonal grey model with dynamic seasonal adjustment factors. Then the lifespan distribution of DESWHs is fitted based on the survey data, and the quantity of wasted DESWHs is estimated from 2012Q1 to 2038Q4. Finally, on the basis of the data crawled from the internet, the weight distribution of DESWHs is constructed, and the recycling value of wasted DESWHs is then calculated. The empirical results show that the waste quantity of DESWHs will increase greatly from 2012Q1 to 2022Q4 and that the recycling value of wasted DESWHs may be worth 18.48 billion yuan in China. The results show that the wasted DESWHs have a great recycling value, and that the proposed multi-data source based hybrid methodology can be used as an effective estimation method for the recycling value of electronic waste.